Material system analysis: Characterization of flows, stocks, and performance indicators of manganese, nickel, and natural graphite in the EU, 2012–2016. (8th January 2022) - Ciacci, Luca; de Matos, Cristina T.; Reck, Barbara K.; Wittmer, Dominic; Bernardi, Elena; Mathieux, Fabrice; Passarini, Fabrizio
Abstract: Raw materials form an industrial base to provide the wide range of products and services demanded by industry and society. In particular, manganese, nickel, and natural graphite are examples of materials having a globally consolidated supply chain with interlinked use in steelmaking and essential role in clean energy systems and e‐mobility. A stable material supply chain is hence a priority for import‐dependent regions like the EU and builds upon quantitative system understanding. To this aim, the EU Material System Analysis is applied to analyze the anthropogenic cycle of manganese, nickel, and natural graphite from 2012 to 2016. We provide a detailed characterization of their material stocks, flows, and changes in selected performance indicators including end‐of‐life recycling rate (51% ± 3%, 49% ± 8%, and 8% ± 0% for manganese, nickel, and natural graphite, respectively), self‐sufficiency potential (40% ± 3%, 32% ± 5%, and 5% ± 1%), old scrap ratio (31% ± 0%, 22% ± 2%, and 90% ± 1%), recycling input rate (25% ± 1%, 38% ± 2%, and 3% ± 0%), recycling process efficiency rate (84% ± 2%, 85% ± 6%, and 48% ± 3%), and pre‐consumer losses rate (83% ± 3%, 5% ± 1%, and 24% ± 2%). The achieved results may inform decision‐makers engaged with raw materials recovery and recycling as well as the strategic securement of a reliable material supply to the EU for resilient industrial ecosystems.